Total Hip Arthroplasty for Arthrodesed Hips - M.B. Howard; W.J.M. Bruce; W. Walsh; J.A. Goldberg (Journal of Orthopaedic Surgery, 2002)
The benefits of converting an ankylosed or arthrodesed hip to total hip arthroplasty have been reported in the literature as have the technical difficulties associated with this procedure. 1,2,4 This review, however, outlines the experience of a single surgeon (WJMB) at a single institution using uncemented prostheses. Between November 1991 and June 1996, 5 arthrodesed hips underwent uncemented total hip arthroplasty in 4 males and 1 female. Clinical and radiological follow-up review was for at least three years in all patients. In general, patients were satisfied with the outcome of their surgery with Harris Hip scores improving from an average of 62 preoperatively to an average of 72 postoperatively. The surgical outcome in these difficult cases was not as satisfactory as for routine total hip arthroplasty. Meticulous preoperative planning is required to aim toward leg length restoration and restoration of the abductor moment arm 5 . A modular prosthesis allows versatility at surgery.